Integration Of Responsive Learning Technology In Arabic Language Education: Development Of A Student Interaction Framework - Najmaya Ayu Mustika; Muhammad Khamim As-Syafaat; Ika Rusdiana; Kayyis Fithri Ajhuri (Jurusan Pendidikan Bahasa Arab UIN Kiai Ageng Muhammad Besari onorogo, 2026)
The integration of responsive learning technology has become a crucial component in strengthening student interaction and engagement within higher education, particularly in the context of Arabic language education. The complexity of learning Arabic, which requires continuous practice, interaction, and feedback, demands a digital learning ecosystem that is adaptive, interactive, and responsive to students’ academic needs. In the digital era, higher education institutions are no longer required to provide educational services merely as administrative support, but also as an integral part of the learning process that facilitates communication, interaction, and learning continuity. Customer Relationship Management (CRM) has emerged as a strategic approach that can be adapted to the educational context to support systematic and sustainable student interaction. This study aims to design and develop a responsive learning technology framework based on CRM to enhance student interaction within the Arabic language education ecosystem. The research employed a research and development approach using the ADDIE model, encompassing analysis, design, development, implementation, and evaluation stages. The resulting product is a CRM-based web application implemented in the context of Arabic language education at IAIN Ponorogo. The developed framework integrates multiple interaction touchpoints involving students, lecturers, and study program administrators to support learning-related communication, academic monitoring, and service responsiveness. The effectiveness of the system was evaluated through small-scale and limited large-scale classroom trials. The results of the small-scale trial obtained a score of 79.4, while the limited large-scale trial achieved a score of 83, indicating that the system is categorized as “good.” These findings demonstrate that the integration of CRM-based responsive learning technology can effectively support student interaction, enhance learning responsiveness, and contribute to the development of a cohesive digital learning ecosystem in Arabic language education.